STRATEGI MARKETING PENERIMAAN MAHASISWA BARU UNIVERSITAS SANGGABUANA BANDUNG DITENGAH PANDEMI COVID 19 - Y. Ony Djogo (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2020)
Indeed, currently we are experiencing a difficult situation, but the process of admitting new students must also continue for the sustainability of the campus and also learning in Indonesia, especially on USB. With campus technology, it can facilitate the admission of new students, provide sophisticated services, such as PMB, payments, academics, learning etc. After simplifying the process of receiving and payment, what to do next is Promotion. Because in the current situation conventional promotion is not possible, one solution is to take advantage of digital technology that is easily accessible to many people. Here's what can be done with promotion with digital marketing: Use the website to be recognized more quickly, Make video ads on YouTube, Content marketing and SEO optimization, Take advantage of the campus search platform.